Optimal structural design : contact problems and high-speed penetration - Banichuk, Nikolay Vladimirovich; Ivanova, S. I︠U︡ (De Gruyter, 2017)
"This monograph studies optimization problems for rigid punches in elastic media and for high-speed penetration of rigid strikers into deformed elastoplastic, concrete, and composite media using variational calculations, tools from functional analysis, and stochastic and min-max (guaranteed) optimization approaches with incomplete data. The book presents analytical and numerical results developed by the authors during the last ten years"- Resumé vydavatel
Keywords: kontaktní mechanika; stavební mechanika; fázová rozhraní; styčníky; contact mechanics; structural mechanics; interfaces (physical sciences); joints (engineering); elektronické knihy; monografie; electronic books; monographs